Dream-reality confusion in borderline personality disorder: a theoretical analysis - Skrzypińska, Dagna; Szmigielska, Barbara D. (Frontiers in Psychology, 2015)
This paper presents an analysis of dream-reality confusion (DRC) in relation to the characteristics of borderline personality disorder (BPD), based on research findings and theoretical considerations. It is hypothesized that people with BPD are more likely to experience DRC compared to people in non-clinical population. Several variables related to this hypothesis were identified through a theoretical analysis of the scientific literature. Sleep disturbances: Problems with sleep are found in 15-95.5% of people with BPD (Hafizi, 2013), and unstable sleep and wake cycles, which occur in BPD (Fleischer et al., 2012), are linked to DRC. Dissociation: Nearly two-thirds of people with BPD experience dissociative symptoms (Korzekwa and Pain, 2009) and dissociative symptoms are correlated with a fantasy proneness; both dissociative symptoms and fantasy proneness are related to DRC (Giesbrecht and Merckelbach, 2006). Negative dream content: People with BPD have nightmares more often than other people (Semiz et al., 2008); dreams that are more likely to be confused with reality tend to be more realistic and unpleasant, and are reflected in waking behavior (Rassin et al., 2001). Cognitive disturbances: Many BPD patients experience various cognitive disturbances, including problems with reality testing (Fiqueierdo, 2006; Mosquera et al., 2011), which can foster DRC. Thin boundaries: People with thin boundaries are more prone to DRC than people with thick boundaries, and people with BPD tend to have thin boundaries (Hartmann, 2011). The theoretical analysis on the basis of these findings suggests that people who suffer from BPD may be more susceptible to confusing dream content with actual waking events.